RAISING TRAFFIC AWARENESS IN SOCIETY - Abd Asis; Slamet Sampurno S; Dara Indrawati; Siti Isti Dwi Pratiwi; Ervinadia Ghita Syahfitri (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
Lack of legal compliance of the people of Moncongloe Village, Moncongloe District, Maros Regency Against Traffic According to Law No. 22 of 2009, the activities of the Community Service Program, Partnership Program - Hasanuddin University (PPMU-PK-M) Hasanuddin University Research and Community Service Institute (LP2M Unhas) can become a forum for the community and village officials to increase awareness and legal compliance in form of providing education and legal understanding of Traffic According to Law No. 22 Year 2009.